Study on the Properties of Epoxy Composites Using Fly Ash as an Additive in the Presence of Nanoclay: Mechanical Properties, Flame Retardants, and Dielectric Properties - Tuan Anh Nguyen; Thi Mai Huong Pham (Journal of Chemistry)
Small and light fly ash is a by-product of thermal power plants, in which oxides mainly present in fly ash are suitable to reinforce composite materials. Its content accounts for 10, 20, 30, 40, and 50% of those materials. However, due to the smooth surface, it cannot stick completely in plastics. Therefore, in this work, it was studied to combine nanoclay additive (I.30 E) with 1, 3, and 5% by weight to synergize to improve mechanical strength, fire retardation, and electrical properties. Mechanical properties and flame retardant properties have improved markedly. At the combined ratio of 40% by weight of fly ash and 3% nanoclay, nanocomposites have tensile strength values of 64.12 MPa, flexural strength of 89.27 MPa, compressive strength of 215.23 MPa, and impact resistance of Izod 14.45 kJ/m2, oxygen index limited to 26.8% of fire retardant material. In terms of dielectric strength, the electric strength of pure epoxy is 17.5 kV/mm, higher than that before adding nanoclay (12.7 kV/mm). The presence of nanoclays in the material creates a tortuous electric path, slowing the propagation of the power plant, which is the main factor that improves the breaking strength of the nanocomposite.